Emerging rurality: rethinking the city based on valuation of the urban-rural - Rocha , Emanuela Alves da; Araujo , Eloisa Carvalho de (Revista Nacional de Gerenciamento de Cidades, 2023)
The development of urban and rural environment concepts pervades landscape characteristics and the dichotomous relationship between these areas. The urban and rural understandings are related to their economic, industrial, and agrarian activities to the city and countryside, respectively. Thus, the urban-rural duality departs the notion of a city that includes multiple environments and induces both an erasure of the ecosystem logic of humans and nature relations and consideration of humans as part of its decrease. In that regard, aspects connected with the dynamic of products and services store, such as water and food provisions, have unstuck from their origins which trivializes the process of production, supply, and consumption. Furthermore, a discussion between urban and rural must consider several points, including food sovereignty, agribusiness, land access inequality, local and regional territorial articulation, and climate. Based on a bibliographic review of academic articles published in journals, periodicals and events, this article intends to ponder these aspects in defence of an idea of urban-rural interdependence from the conception of the urban revolution and the urban phenomenon concept. Besides, this study seeks to strengthen the debate on consolidated and conflicted territorial practices aimed to rethink new public policies toward a more integrated and less unequal territory.